End‐of‐Trial Health Outcomes in Look AHEAD Participants who Elected to have Bariatric Surgery. Issue 4 (21st March 2019) - Wadden, Thomas A.; Chao, Ariana M.; Bahnson, Judy L.; Bantle, John P.; Clark, Jeanne M.; Gaussoin, Sarah A.; Jakicic, John M.; Johnson, Karen C.; Miller, Gary D.; Unick, Jessica L.; Yanovski, Susan Z.; ,
Abstract : Objective: This study examined end‐of‐trial health outcomes in participants in the Action for Health in Diabetes (Look AHEAD) trial who had bariatric surgery during the approximately 10‐year randomized intervention. Methods: Data were obtained from the Look AHEAD public access database of 4, 901 individuals with type 2 diabetes and overweight/obesity who were assigned to intensive lifestyle intervention (ILI) or a diabetes support and education (DSE) control group. Changes in outcomes in participants who had bariatric surgery were compared with those in participants with BMI ≥ 30 kg/m 2 who remained in the ILI and DSE groups. Results: A total of 99 DSE and 97 ILI participants had bariatric surgery. At randomization, these 196 participants were significantly younger and more likely to be female and to have higher BMI than the remaining ILI ( N = 1, 972) and DSE ( N = 2, 009) participants. At trial's end, surgically treated participants lost 19.3% of baseline weight, compared with 5.8% and 3.3% for the ILI and DSE groups, respectively, and were more likely to achieve partial or full remission of their diabetes. Conclusions: The large, sustained improvements in weight and diabetes observed in this self‐selected sample of surgically treated participants are consistent with results of multiple randomized trials.